Discrimination, Harassment and Racism in Finnish Lower Secondary Schools - Tuomas Zacheus; Mira Kalalahti; Janne Varjo; Minna Saarinen; Markku Jahnukainen; Marja-Liisa Mäkelä; Joel Kivirauma (DE GRUYTER POLAND, 2025)
In this article, we examine the experiences of students in the ninth grade (aged 15-16 years) in relation to harassment, discrimination and racism. The study was carried out at eight Finnish lower secondary schools with a high proportion of students with an immigrant background in 2015. The sample consisted of survey data (n = 445) and thematic interviews (n = 112) conducted with young people of Finnish and immigrant origins. Approximately one-quarter of the respondents said that they had been harassed or discriminated against at schools, and one-tenth had experienced this behaviour in their free time. In addition, almost half of the young people thought that discrimination is widespread in Finland. The more often a student experienced discrimination, the less they liked school. Experiences of harassment, discrimination and racism were especially downplayed when the respondent was the target.